Effect of gge on the recruitment of oocytes in the climbing perch, Anabas testudineus (Bloch) (Bangladesh Journal of Zoology, 2015)
Effect of age on the recruitment of oocytes in Anabas testudineus has been studied. For age determination opercular bones, otoliths and scales were collected from 210 adult females weight ranging between 18.0 g and 135.0 g and length between 8.5 cm and 20.5 cm. The scatter points of opercular bone length, scale length, and otolith length against the fish length showed linear relationships. The high values of coefficient of correlation (r) indicated that all hard parts grew proportionately with the corresponding growth of the fish. The marginal open zone in all hard parts had minimum width during the months of June and July indicating that the age ring might have been formed in the season immediately preceding these months due to spawning. The age rings were annulus in nature since the fish was found to spawn once in a year. Recruitment of oocytes were not affected by the age of the fish. No statistical significant difference was observed between the number of oocytes contained in the ovary of fishes falling into two different groups of the same body length.Bangladesh J. Zool. 43(1): 27-36, 2015